Ebraismo e caste in India: la tensione tra halacha, cultura locale e colonialismo - Gardella Tedeschi, Bianca (Riflessioni di metodo sul diritto comparato delle religioni, 2017)
The article addresses the issues of Judaism and caste system in India. The first paragraphs offer a short introduction on the history of the various Jewish settlements in India from the second century BCE to the colonial period. The historical introduction is the base to understand the relation of the Jews with their Indian neighbors: Jews, even in the older settlements, positioned themselves towards the other castes as a caste in itself, in order to achieve a higher ranking and status in the Indian society. The following paragraphs show how the caste system percolated within the different communities but has never been accepted by the halakha. The last paragraph describes how, recently, groups of Dalits have asserted their belonging to Judaism and how halakha considers their assertions.